Knowledge and willingness of parents towards child girl HPV vaccination in Debre Tabor Town, Ethiopia: a community-based cross-sectional study - Gedefaye Nibret Mihretie; Tewachew Muche Liyeh; Alemu Degu Ayele; Habtamu Gebrehana Belay; Tigist Seid Yimer; Agernesh Dereje Miskr (BMC, 2022)
Plain language summary Infection with the Human Papillomavirus (HPV) causes nearly 99% of cervical cancer cases and more than 20% of breast, neck, and anogenital cancers. The HPV vaccines protect against high-risk types of HPV (types 16 and 18), which account for approximately 70% of cervical cancers. Global coverage of the HPV vaccine was 39.7%, with high-income countries (68%), middle-income countries (28%), and lower-middle-income countries (2.7%). For different reasons, cervical cancer screening is very poor in Ethiopia (below 2%). Cervical cancer is mostly asymptomatic more than 20 years after infection. Primary prevention (enhancing the HPV vaccine) is the best way to protect women from cervical cancer. Adolescents' uptake and acceptance of the vaccine depend on parental consent. Assessing parental knowledge and willingness at a community level is very crucial. A simple random sample technique was used to include 638 participants. A structured and pre-tested face-to-face interviewer-administered questionnaire was used to collect the data. The data were entered and analyzed using Epi-Data, and SPSS software, respectively. Bivariate and multivariable analyses were used to examine the association. Nearly one-third (35.4%) and less than half (44.8%) of participants were knowledgeable and willing to receive the HPV vaccination. The knowledge and willingness of the parents are significantly lower. Being government employees and having a family history of sexually transmitted diseases (STD) were factors affecting the knowledge of parents about the human papillomavirus vaccine. Participants' age, secondary education and above, fear of HPV infection, and having good knowledge of the HPV vaccine were significantly associated with their willingness to use the HPV vaccine. The knowledge and willingness of the parents are significantly lower. Health officials and stakeholders should scale up HPV vaccine promotion through public media.